Stress characteristics and stress reversal mechanism of white birch (Betula platyphylla) disks under different drying conditions - Fu, Zongying; Zhao, Jingyao; Lv, Yangyi; Huan, Siqi; Cai, Yingchun (Maderas. Ciencia y Tecnología, 2016)
Drying stress is the main cause for the generation of drying cracks in wood disks during drying, which limits the processing and utilization of this valuable material. For this study, white birch disks with one trunk and a thickness of 30 mm were dried under three different drying conditions: 1) a very slow drying process preventing the generation of a radial moisture content (MC) gradient, 2) a drying process with slowly increasing temperature leading to a radial MC gradient, with a higher MC in the heartwood, and 3) the same heat drying process but the wood disks were partly covered with a thin plastic film prior to the drying process leading to a reversed radial MC gradient, i.e., a higher MC in the sapwood. For each drying condition, the tangential elastic strain in the wood disks was investigated for a mean MC of 26%, 18% and 10%, respectively, as a function of the radial distance from the pith in order to predict the drying stress. Furthermore, the stress characteristics and stress reversal mechanisms in wood disks are discussed in this paper with the help of stress analysis sketches.